Honeymoon - Patterson, James; Roughan, Howard (London : Headline Publishing, 2011)
When a number of rich men come to a mysterious end, and a young investment banker dies of a supposed heart attack, FBI agent John O'Hara believes it is the work of a cold-blooded killer. Turning his eye to the only witness - the young banker's beautiful and secretive widow - O'Hara thinks he's closing in, but he's not sure whether he's pursuing justice or his own fatal obsession.
Keywords: Investment bankers -- Crimes against -- Fiction; Detective and mystery fiction